"Do Not Remember the Former Things". (October 2016) - Rynkiewich, Michael A.
There are times when God says "Remember, " and times where God says "Do not remember." Discerning the times is a constant requirement in mission studies and practice. The times are changing, and so are the means of interpreting the times. Urbanization, globalization, migration, and diaspora have created a world that, in many ways, is unlike any we have seen before. In missiology, updating our methods of doing research offers the best chance to reshape our models and mottoes for mission.